Souffrir la perte de ses capacités: une expérience dévoilant la nature paradoxale de l’existence humaine - Dubois, Alain; Ratté, Jimmy (Canadian Journal of Counselling and Psychotherapy, 2008)
The article proposes an understanding of an individual’s experience of loss of capacity from an existential perspective, starting from the human desire to live in denial of the existence of vulnerability, referring to the concept of Becker’s immortality project (1973). The inescapable experience of finitude is then presented as a kind of questioning, often drastic, of the illusion of invulnerability. Deprived of the protection of the usual way of conceiving and interacting with the world, the individual gains access to the paradoxical nature of existence (Schneider, 1999). The revelation process manifests itself in experiences described in contradictory terms, both as a source of distress and of development.